AN ERROR ANALYSIS IN THE USE OF PUNCTUATION IN NARRATIVE TEXT AT SECOND GRADE OF SMA NEGERI 1 MAKASSAR - Dea Rezky Amelia; Andi Tenri Ampa; Ilmiah Ilmiah (Universitas Muhammadiyah Makassar, 2018)
The research was aimed to find out the kinds of errors in the use of punctuation in narrative text at second grade of SMA Negeri 1 Makassar. The research focused on five punctuation, they are full stop, comma, question mark, exclamation point, and quotation mark. The method of this research was descriptive quantitative. The subjects of this research took 36 students from 4 classes, it used random sampling technique. The researcher used narrative text as instrument. From the result, there are some kinds of errors students made, they are Misordering, omission, and addition of punctuation. Omission of full stop was dominant error made by students that is 19.22%. In writing, punctuation is very important because it can make reader understand the meaning of writing.